Klang Consumer’s Willingness to Pay (WTP) for Malaysian Good Agricultural Practices (myGAP) Certified Vegetables - Logeswary Kalyana Sundram; Nitanan Koshy Matthew (SAGE Open)
Malaysian Good Agricultural Practices (myGAP) promote the environmentally friendly production of vegetables. However, consumers lack awareness and knowledge about myGAP-certified vegetables; thus, their willingness to pay for sustainably produced myGAP vegetables remains unknown. Hence, this research aimed to (a) identify the level of consumers’ awareness, knowledge and purchasing behavior when purchasing myGAP-certified vegetables in Klang, (b) determine the factors influencing consumers’ WTP for myGAP certified vegetables in Klang, and (c) estimate the consumers’ WTP for myGAP certified vegetables. Three hundred and fifty-seven respondents were selected using convenience sampling with a Double-Bounded Dichotomous Choice (DBDC) questionnaire. The result indicated that most respondents had high awareness and purchasing behavior levels and medium-level knowledge about purchasing myGAP-certified vegetables in Klang. Gender, income, and behavior influenced the consumers’ WTP for myGAP-certified vegetables. The findings revealed that the consumers were willing to pay, on average, an additional amount of RM 1.58/USD 0.34 using the logistic regression, while between RM 3.47/USD 0.76-RM 6.33/USD 1.40 using bivariate probit regression for myGAP vegetable as compared to the traditional vegetables using tomato as a representative. The findings of this study aimed to create awareness among consumers of the myGAP-certified products.